OpEd: The Future Factory - Jenny Andersson (economic sociology_the european electronic newsletter, 2019)
In Nathaniel Rich's novel Odds Against Tomorrow, a futurist by the name of Mitchell Zukor is born from the ashes of Seattle, the city devastated by fire. In the wake of the Seattle disaster, American corporations turn to a new industry, the future industry, no longer in the realm of assuring financial futures but in the business of insuring social and economic futures in the face of impending climate apocolypse.
Keywords: 300